Isolation and Selection of Duck Primary Cells as Pathogenic and Innate Immunologic Cell Models for Duck Plague Virus - Tian, Bin; Cai, Dongjie; He, Tianqiong; Deng, Liyao; Wu, Liping; Wang, Mingshu; Jia, Renyong; Zhu, Dekang; Liu, Mafeng; Yang, Qiao; Wu, Ying; Zhao, Xinxin; et al. (Frontiers in Immunology, 2020)
Duck plague virus (DPV) is a representative pathogen transmitting among aquatic animals, it causes gross lesions and the immune inhibition in geese and ducks. The mechanism of the organ tropism and innate immune evasion of DPV is not completely deciphered, since the lack of cell models to study the innate immune manipulation and pathogenicity of aquatic virus or other microbes. In the present study, we isolated five types of duck primary cells, DEF, neuron, astrocyte, PBMC and macrophages. In order to select a better cell models for DPV, tropism infection and innate immunologic assays were executed on these primary cells. Firstly, they responded differently to the stimulation of DNA virus or RNA virus analogues. Secondly, DPV infection was wide tropism, as the recombinant virulent strain (CHv-GFP) infected DEF, neuron, astrocyte and macrophage, but not the PBMC since the expression of EGFP was negligible. The basal level of innate immune molecules are highest in macrophage, but lower in DEF and astrocyte. Conversely, the viral titer and genomic copy numbers of the attenuated strain was higher in DEF and astrocyte than that in neuron and macrophage. The viral titer and genomic copy numbers of attenuated strain was higher than the virulent strain in DEF, neuron and astrocyte. While the innate immune response was not significantly induced by both the strains of DPV in DEF, neuron and astrocyte. The virulent strain persistently, but the attenuated strain abortively, infected the macrophage, along with the phenomenon of innate immune being inhibited or activated by virulent strain or attenuated strain, respectively. Blockage of the IFNAR signaling promoted the viral replication of attenuated strain. Pre-activation the IFNAR signaling restricted the virulent strain infection. These selection assays indicated that induction of innate immune plays an essential role in controlling DPV infection, and macrophages are an important cell model for further investigation. Our study provided practicable and feasible methods to isolate and culture the duck primary cells, they will facilitate the investigation in the mechanism of organ tropism, innate immune responses, latency infection and antiviral drugs of DPV, and maybe other aerial bird pathogens.